Batik discharge printing on lyocell, linen (flax) polyester & polyester/cotton blend fabrics / Mohd Rozi Ahmad, Wan Yunus Wan Ahmad and Siti Marsinah Tumin - Ahmad, Mohd Rozi; Wan Ahmad, Wan Yunus; Tumin, Siti Marsinah (2005)
Malaysian batik has traditionally used wax as physical resist to create designs on cotton, silk and rayon fabrics. An alternative printing style called discharge printing is explored in this study as it is able to produce white and colored sharply outlined patterns which are characterized by close-fitting, fine details and small motifs on contrasting color (usually darker) ground shade that would otherwise be virtually impossible to obtain by conventional printing style. The printing was done on several fabric materials: linen (flax), lyocell, polyester and polyester/cotton blend fabrics. The luxurious, elegant and comfortable properties of lyocell and linen could replace traditional batik fabrics as exclusive batik products. Polyester and polyester/cotton blend fabrics should be considered as alternative fabrics for batik application because of their competitiveness in price, durability and color fastness in comparison with traditional batik fabrics of cotton, silk and rayon. The printing techniques carried out were screen printing and canting. The fixation methods applied on the printed fabrics were dry heat and ironing. The result of different printing techniques and different methods of fixation were compared.